Hedonism as an Ideological Challenge to the ʿAqidah of the Muslim Ummah in the Digital Media Era - Haswira Salleh Ahim (Penerbit Hellow Pustaka, 2026)
The development of modern culture and the influence of digital media have transformed hedonism from a purely philosophical debate into a lifestyle that emphasizes self-gratification, unrestricted freedom, and the prioritization of personal desires. This phenomenon becomes problematic when pleasure is regarded as the primary measure of life success, as it potentially conflicts with the Islamic value system and ʿaqidah. Accordingly, this article aims to analyze modern hedonism and examine its distinctions from an Islamic perspective. This study adopts a qualitative library-based approach by analyzing classical and contemporary texts, as well as academic articles in the field of Islamic thought. The findings indicate that modern hedonism has shifted from an ethical theory to a way of life oriented toward pleasure and individual freedom, whereas Islam situates human life within a framework of tawḥīd, responsibility, and self-discipline. This contrast demonstrates that modern hedonism carries significant ideological implications for the formation of Islamic values and identity, thereby necessitating a stronger Islamic understanding in addressing contemporary cultural challenges.